Care giving to dependent people. A source of jobs in times of crisis. The case of Spain - Camacho Ballesta, José Antonio; Ruiz Peñalver, Soraya María; Miguela Recover, María de los Ángeles (Cuadernos de Relaciones Laborales, 2015)
Ageing of European and Spanish populations in recent decades reflects natural demographic evolution triggered by even greater longevity of senior citizens, and falling birth and fertility rates. Such evolution warrants greater social protection for dependent people, including not only people with disabilities but also elderly citizens whose dependency makes them vulnerable. Spain’s expanding social safety network has identified several economic activities to provide care for dependent people who for various reasons require specific types of attention. Such activities require a growing supply of services to fulfill likewise expanding social demand to meet related specific needs. But they have also, and contrary to many other activities, created jobs despite the present financial and economic crisis marked by job destruction. Against this backdrop, our paper shows care giving for dependents can create jobs even under conditions of a deep crisis that is having serious consequences in the labour market.
Keywords: dependents; elderly; employment; labor market; social services and employment sources.